Nilai-Nilai Aswaja dalam Bioekonomi Kehutanan: Kerangka Konseptual Penguatan Modal Sosial Berbasis Nilai Menuju Indonesia Emas 2045 - Mahfudz Mahfudz; Khulfi M. Khalwani; Dodi Sumardi; Faridh A U Hamdani (CV. AFDIFAL MAJU BERKAH, 2026)
The transition toward a sustainable forest bioeconomy requires not only technological innovation and institutional capacity but also ethical values that strengthen collaboration and collective action. This study aims to develop a conceptual framework that integrates Ahlussunnah wal Jama'ah (Aswaja) values into forest bioeconomy by positioning them as the normative foundation of value-based social capital. A qualitative approach was employed using an Integrative Literature Review (ILR), synthesizing 37 scientific publications and four Indonesian policy documents through content analysis and thematic synthesis. The findings indicate that Aswaja values—tawassuṭ (moderation), tawāzun (balance), tasāmuḥ (tolerance), i‘tidāl (justice), and maṣlaḥah (public benefit)—provide an ethical basis for strengthening trust, reciprocity, institutional legitimacy, and collective action in community-based forest governance. Building on these findings, the study proposes a conceptual model in which Aswaja values function as the normative foundation, value-based social capital serves as the institutional mechanism, and forest bioeconomy acts as the strategic instrument for achieving sustainable development outcomes. The model extends existing forest bioeconomy literature by integrating ethical, institutional, and socio-economic dimensions into a unified analytical framework. It also offers practical insights for policymakers, Social Forestry practitioners, and community organizations seeking to promote inclusive, resilient, and sustainable forest-based development in support of Indonesia Emas 2045